Intracranial pressure monitoring in patients with spontaneous onset of orthostatic headache - Linda D’Antona; Sanjay Cheema; Dwij Mehta; Fion Bremner; Laurence Dale Watkins; Ahmed Kassem Toma; Manjit Singh Matharu (The Journal of Headache and Pain)
Abstract Background Spontaneous intracranial hypotension (SIH) is a debilitating disorder, with an estimated annual incidence of 3.7 per 100,000. Diagnosing SIH can be challenging for clinicians, as patients frequently present with normal investigation findings. Intracranial pressure (ICP) monitoring has been proposed as a valuable tool for patients with orthostatic headaches that are highly suggestive of SIH but have inconclusive investigation results. The primary objective of this study was to determine the proportion of patients with spontaneous orthostatic headaches and normal diagnostic work-up who exhibited abnormal ICP monitoring results. Methods This single-centre, retrospective observational study was conducted at a tertiary referral centre specialising in SIH and CSF dynamics disorders. Consecutive patients with spontaneous orthostatic headaches and inconclusive diagnostic work-up who underwent 24-hour ICP monitoring were considered eligible. The 24-hour ICP monitoring followed a standardised protocol, measuring median ICP and pulse amplitude (a marker of brain compliance) during the daytime, nighttime, and over the entire 24-hour period. Specific cut-offs for low and high ICP states were predetermined based on the best available current evidence. Results Thirty-eight patients (23 females, mean age 41 years ± 14SD) were identified. All patients had orthostatic headaches with a spontaneous onset. The mean duration of symptoms was 46 months ± 36SD. ICP monitoring identified 3 patients (7.9%) with low ICP (mean of the median 24-hour ICP − 2 mmHg ± 2SD) and 6 patients (15.8%) with high ICP (mean of the median 24-hour ICP 9 mmHg ± 3SD). Obvious CSF dynamics disturbances were excluded in the remaining 29 patients (76.3%, mean of the median 24-hour ICP 3 mmHg ± 3SD). The only clinical feature that was more common in patients with abnormal ICP compared to patients with normal ICP results was audiovestibular disturbance, namely aural fullness or muffled hearing (67% versus 17%, p = 0.015). There were no complications from the ICP monitoring procedure for any patient. Conclusions When appropriately selected, patients with a clinical picture highly suggestive of SIH, who have a negative diagnostic work-up, may benefit from consideration of invasive ICP monitoring. Moreover, a significant minority of patients with orthostatic headache may paradoxically have a high CSF pressure state, which can be detected using ICP monitoring. Meeting presentations Portions of this work were presented in abstract and oral presentation form at the Twenty-eighth Anglo-Dutch Migraine Association meeting (08/06/2018), the Tenth Meeting of the International Society for Hydrocephalus and Cerebrospinal Fluid Disorders (20/10/2018; Bologna, Italy), the Society of British Neurological Surgeons 2018 Autumn Meeting (19/09/2018; London, United Kingdom), and the European Association of Neurosurgical Societies 2023 congress (27/09/2023; Barcelona, Spain). This work is also part of the doctoral thesis of one of the authors (LD).